A CRITICAL LEGAL STUDY ON SURROGACY WITH SPECIAL REFERENCE TO GENDER JUSTICE - Chavan, Amruta Arjun (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The ultimate goal of the Indian constitution is to uphold each person's dignity while preserving the nation's unity and integrity by guaranteeing justice, liberty, equality, as well as fraternity to all Indian citizens. One of the goals of the Constitution of Indian is to guarantee to the people, the citizen of India by providing justice which includes social justice, economic justice, and political justice. Law is a tool to attain justice, not an end in and of itself. The definition of ‘social justice’ is all-encompassing. Gender Justice is also included. With the development of the ICT industry, the word ‘gender justice’ has assumed new meanings and forms. Due to the numerous social, legal, economic, cultural, and legal problems involved, the Surrogacy (Regulation) Act of 2021 and the Assisted Reproductive Technology Act, 2021 are heavily criticized and challenged. The Indian Constitution guarantees social justice as a fundamental right. Gender justice is a human right as well as a fundamental one. The goal of law is to promote justice; it is not an end in and of itself. The researcher will be concentrating on the idea of surrogacy and the problems associated with it, particularly from the standpoint of gender justice, in this study paper and others. The researcher has chosen to use a doctrinal research approach, and their methodology will be critical research.